2018
DOI: 10.1590/1982-021620182028616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain threshold upon palpation of the masticatory muscles in women with temporomandibular disorder according to the Research Diagnostic Criteria of Temporomandibular Disorders

Abstract: Purpose: to evaluate the pain threshold upon palpation of the masticatory muscles in women with temporomandibular disorder (TMD) according to the Research Diagnostic Criteria of Temporomandibular Disorders (RDC/TMD). Methods: a cross-sectional study was conducted involving the evaluation of pain threshold upon palpation of the extraoral muscles (temporal, masseter, posterior mandibular region, submandibular region) and intraoral muscles (lateral pterygoid area and temporal tendon) in women using the RDC/TMD cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
1
1
Order By: Relevance
“…[29], [30]. Some research suggests a greater frequency and longer duration of post-endodontic pain in females, [20], [22] while others [28].find that males have longer suffering than females.No significant connection was discovered between patient-related characteristics and postoperative pain, including gender, in the current investigation [14]. Subjectivity is an issue when analyzing pain.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…[29], [30]. Some research suggests a greater frequency and longer duration of post-endodontic pain in females, [20], [22] while others [28].find that males have longer suffering than females.No significant connection was discovered between patient-related characteristics and postoperative pain, including gender, in the current investigation [14]. Subjectivity is an issue when analyzing pain.…”
Section: Discussioncontrasting
confidence: 53%
“…The literature indicates a great variability of postoperative pain results that can range from 3-58% [12].This high level of variability can be attributed to the startling variations in treatment protocols, pulp and periradicular conditions, and postoperative assessment methods that were found between investigations. Several research have examined the impact of root canal sealers on post-operative discomfort, In a split-mouth randomized clinical experiment, Graunaite et al [14] observed that 35% of the patients reported feeling discomfort from their apical periodontitis in single-rooted teeth that had previously had endodontic treatment [13], [14].…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados obtidos na avaliação dos músculos temporal, masseter e pterigoideo, de acordo com a sintomatologia dolorosa, corroboram com estudos realizados em uma clínica de fisioterapia localizada na cidade de São Paulo, nos quais foi demonstrada a relevância do exame clínico nestes mesmos músculos de forma bilateral. Tais músculos evidenciam representatividade dolorosa no reconhecimento da DTM, podendo gerar potencial sobrecarga articular, bem como aumento da atividade muscular e desordens oclusais 21 .…”
Section: Discussionunclassified
“…A frequent approach in the relevant literature concerning MFP diagnostics was application of the quantitative algometric pain measurement, with comparative VAS measurements [8,17]. The algometry is warmly recommended as an examination method in different scientific studies.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the manual muscle palpation is established as the "gold standard" and is still the most frequently applied method for examination of muscle sensitivity [7,8]. However, the attitude that it is exclusively sufficient for diagnosing the masticatory MFP can mostly be found in older papers and, nowadays, it is considered outdated.…”
Section: Applicability Of the Instruments For Measuring Pain Intensitmentioning
confidence: 99%